Removal of Azo Dyes Orange II and Reactive Black 5 from Aqueous Solutions by Adsorption on Chitosan Beads Modified with Choline Chloride: Urea Deep Eutectic Solvent and FeO - Óscar Martínez-Rico; Lucía Blanco; Ángeles Domínguez; Begoña González (Separations, 2023)
The removal of the azo dyes Orange II (OII) and Reactive Black 5 (RB5) from aqueous solutions was studied using three types of adsorbents derived from chitosan: unmodified chitosan beads (un-Ch), chitosan beads tuned with a deep eutectic solvent (DES) composed of choline chloride:urea at a 1:2 molar ratio (Ch-DES), along with FeO nanoparticles added to chitosan and modified with DES (Ch-FeO-DES). Both dyes were effectively removed in 3–4 h when Ch-DES beads were used, at a dye concentration range of 25–50 mg/L. The modification with DES improved the removal efficiency to achieve increases of around 32% for OII and 17% for RB5. The adsorbent dosage and the initial dye concentration influenced the adsorption process. Isotherm adsorption models (Langmuir, Freundlich, and Temkin) and kinetic models (pseudo-first-order, pseudo-second-order, intraparticle diffusion, and Elovich models) were applied to identify the adsorption behavior. The process could be characterized by employing the pseudo-second-order kinetic model and fitting it to the monolayer Langmuir isotherm. The adsorption occurred on a monolayer with no interaction among dye molecules when electrostatic forces would determine the attaching of dye molecules on the adsorbent. OII was efficiently desorbed by an alkaline solution, while RB5 was more strongly attached. The adsorbent could be recycled, after regeneration with an acid solution, for at least 5 reuse cycles while still achieving effective OII removal. Reactivation with a diluted EDTA solution allowed the authors to recycle RB5-attached beads, achieving optimum removal in two further uses.